PERAN FASILITAS SARANA DAN PRASARANA SSB PASPEL BATHIN II PELAYANG - Juranda; Ikhsan Maulana Putra; Raja Bani Pilitan (Master of Physical Culture and Recreation in Nusantara, 2025)
Abstract: This research is motivated by the important role of facilities and infrastructure in supporting the quality of early-age football coaching. SSB PASPEL Bathin II Pelayang, as one of the football schools in a rural area, faces various limitations in facilities, ranging from the limited number of training equipment, the condition of the field which is not yet fully adequate, to the absence of changing rooms, toilets, and lighting. This study aims to determine the actual condition of facilities and infrastructure, the level of their utilization in the coaching process, and the extent of their role in improving the quality of football coaching at SSB PASPEL Bathin II Pelayang. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The informants in this study consisted of one coach and four students of SSB PASPEL Bathin II Pelayang. Data were analyzed using an interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that: (1) the condition of facilities and infrastructure at SSB PASPEL Bathin II Pelayang is still very limited. The field is of standard size, but its maintenance is not optimal; training facilities such as balls, cones, and bibs are limited in number; and supporting infrastructure such as changing rooms, toilets, and lighting is not available; (2) the utilization of facilities and infrastructure is carried out optimally, but the limited quantity reduces the effectiveness of training because students must take turns using the equipment; (3) facilities and infrastructure play a significant role in supporting the quality of coaching, but the existing limitations reduce comfort, safety, and students’ motivation